Escalating complexity and fragmentation of mental health service systems: the role of recovery as a form of moral communication. Issue 5 (21st May 2021) - Weaver, Nicholas
Abstract : Purpose: Theoretical generalisation provides the basis for tackling problems of service complexity, fragmentation and disrupted care pathways. Design/methodology/approach: Recent mental health service transformation in Wales, United Kingdom, has been stimulated by a policy programme underpinned by person-centred recovery values. This paper offers analysis informed by the perspectives of Niklas Luhmann and other noted theorists to examine escalating service system complexity related to this transformation. Analysis builds upon the findings of a qualitative study employing thematic discourse analysis of talk of people with mental illness and associated workers. Findings: In total, three themes were constructed in participants' talk: "Competing versions of recovery", "Misaligned service expectations" and "Disrupted care pathways." Recovery may be understood as a form of moral communication and autopoietic meaning-making activity, according to Luhmann's radical constructionist epistemology. This has the potential to generate competing versions of recovery, a key contributor to escalating complexity. Research limitations/implications: Findings could be developed further by continued investigation of the relationship between recovery implementation and service fragmentation. Social implications: A more judicious, balanced policy-implementation may cultivate optimal conditions for recovery pluralism by avoiding polarisation towards either top-down, policy-based recovery implementation or a proliferation of approaches at the grassroots level. Findings have implications for healthcare settings beyond the scope of mental healthcare, given the prevalence of person-centred care internationally. Originality/value: A simplistic view of recovery implementation should be challenged. Recovery should not be considered a "magic bullet" for mental healthcare delivery. Haphazard recovery-implementation may have detrimental effects of escalating complexity, service fragmentation and disrupted care pathways.